2019
DOI: 10.3126/nmcj.v21i2.25113
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Neonatal Exposure of Monosodium Glutamate in Kidney of Albino Mice – A Histological Study

Abstract: Monosodium Glutamate (MSG) is a commonly used food additive. Scientists have found that MSG has toxic effects in several tissues and organs like neurons, liver, testes, ovary, kidneys etc due to oxidative stress both after exposure in neonatal period as well as in adult animal models. Although various reports have suggested that MSG has damaging effect in kidneys only few histological studies are available. This study was done to observe any histological changes in kidneys of albino mice after neonatal exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
3
0
1
Order By: Relevance
“…These observations agreed with Bhattacharya et al (19), and Moussa (20) who stated that extensive lipid peroxidation is associated with cellular disorganization, disintegration of membrane integrity and nuclear pyknosis.…”
Section: Discussionsupporting
confidence: 90%
“…These observations agreed with Bhattacharya et al (19), and Moussa (20) who stated that extensive lipid peroxidation is associated with cellular disorganization, disintegration of membrane integrity and nuclear pyknosis.…”
Section: Discussionsupporting
confidence: 90%
“…Bhattachary et al reported that MSG, caused deterioted deteriorated hepatocyte cell membrane, and small and pyknotic nuclei. The researchers also reported a prominent increase in vacuolization of hepatocytes and decreased PAS-positive reaction due to glycogen distribution in hepatocytes [ 49 ]. Waer and Edress administered 60 mg/100 g MSG orally to rats for two months in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Pemilihan jamur tiram menjadi produk penyedap rasa non-MSG ditinjau juga pada kondisi masyarakat Kalimantan Selatan yang akhir-akhir ini banyak beralih menggunakan penyedap rasa non-MSG dikarenakan kesadaran masyarakat akan pentingnya hidup sehat namun tetap menginginkan citra rasa yang kuat pada makanan mereka. Banyaknya efek samping akibat penggunaan penyedap rasa yang mengandung monosodium glutamat (MSG) mengakibatkan potensi jamur tiram sangat tinggi untuk diolah menjadi produk penyedap rasa karena mengandung asam glutamat tetapi rendah sodium dan kalium (Bhattacharya et al, 2011;Sukmaningsih, 2011). Jamur tiram merupakan salah satu jenis jamur yang memiliki kandungan protein cukup tinggi dengan lemak yang rendah, dan kadar serat pangan yang tinggi (Muchtadi, 2010).…”
Section: Pendahuluanunclassified